PROGRAM TAMAN BACA CAHAYA DALAM MENINGKATKAN MINAT BACA MASYARAKAT - Alfi Dwi Safira; Irham Irham; Arrahim Arrahim (Universitas Islam 45 Bekasi, 2022)
The COVID-19 pandemic has forced schools to study at home or study remotely. The Taman Baca Cahaya program aims to increase learning motivation and interest in reading while studying online (online). This program was implemented in a Cahaya Darussalam Housing RW.015/RT.002, Cijengkol Village, Setu District, on February 24-27 2022 called Taman Baca Cahaya. This dedication method uses participation action research. The creation and empowerment of Taman Baca Cahaya is planned for social reflection, participatory planning, and program implementation. The results of this service increase interest in reading and reduce the use of gadgets in children, a means of exchanging information, advancing the world of education and can be a motivation for children to develop reading and thinking skills to face future challenges.